Pengaruh Putaran Terhadap Hasil Pengepresan Kaleng Aluminium Bekas - Icha Arkila Putri; Yudi Setiawan; Firlya Rosa; Adam Zuyyinal Adib; Rodiwan Rodiawan (Jurnal Inovasi Teknologi Terapan, 2026)
One of the factors influencing the performance of the can-pressing machine is the motor speed. This study aimed to determine the effect of machine rotational speed variations on the final height of compressed aluminum cans and the pressing time required. The experiments were conducted using a can-pressing machine powered by a 1 HP electric motor with rotational speed variations of 1200 rpm, 1300 rpm, and 1400 rpm. Each rotational speed was tested in three trials using 10 used aluminum cans as test specimens. The observed parameters were the final height of the cans after pressing and the time required for the pressing process. The results showed that the machine rotational speed significantly affected both the compression height and the pressing time. At 1200 rpm, the average final can height was 18.87 mm with an average pressing time of 36.67 seconds. At 1300 rpm, the average final can height decreased to 17.47 mm with an average pressing time of 20.67 seconds. Meanwhile, at 1400 rpm, the average final can height was 17.02 mm with an average pressing time of 16.67 seconds. These findings indicate that increasing the machine rotational speed results in a lower final can height and a shorter pressing time. Compared with the manual pressing method, which produced a final can height of approximately 30 mm and required about 70 seconds, the machine-assisted pressing process proved to be more effective and efficient. Based on the results of this study, it can be concluded that a rotational speed of 1400 rpm is the optimal operating condition, as it produced the smallest final can height and the shortest pressing time. Therefore, increasing the machine rotational speed within the tested range can improve the quality of the compression results and enhance the efficiency of the used aluminum can pressing process.